Exocrine pancreatic function in juvenile-onset diabetes mellitus. Issue 9 (September 1976) - Frier, B M; Saunders, J H; Wormsley, K G; Bouchier, I A
Abstract : Exocrine pancreatic function was studied in 20 juvenile-onset diabetics, seven maturity-onset diabetics, and five patients with diabetes secondary to chronic pancreatitis. The results were compared with 13 non-diabetic controls. The outputs of bicarbonate, trypsin, and amylase were reduced in the diabetic patients in response to intravenous secretin and CCK-PZ. In the juvenile-onset group, exocrine pancreatic secretory capacity was reduced in 80% of the patients, and the severity of the reduction was related to the duration of the diabetes. The reduction in pancreatic secretory capacity must be taken into consideration when interpreting pancreatic exocrine function in patients with diabetes.